Where is the start of the wrong in these step/s ?
Prove: (sin x)[(cos^3)x] - (cos x)[(sin^3)x] = (1/4)(sin 4x)
Step 1: (sin x)[(cos^3)x] - (cos x)[(sin^3)x] = (1/4)(sin 4x)
Step 2: (sin x)(cos x)[(cos^2)x - (sin^2)x] = (1/4)(sin 4x)
Step 3: (sin x)(cos x)[1-2(sin^2)x] = (1/4)(sin 4x)
Step 4: (sin x)(cos x)(cos 2x) = (1/4)(2sin 2x)(cos 2x)
Step 5: (sin x)(cos x)(cos 2x) = (1/4)(2sin x)(cos x)(cos 2x)
Step 6: 1 = 2 ?
Where is the start of the wrong? :D
Take note: If you get the answer, show your solution/Proof .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I thought 4 1 2 sin 2 x cos 2 x = 4 1 2 ( 2 sin x cos x ) cos 2 x = sin x cos x cos 2 x ?